Assessment of Copper Deficiency In Lambs: A Study From Salah Al-Din City - Ibrahem Jassem, Emtethal; Mohamed Suleiman, Jassim (Journal of Neonatal Surgery, 2025)
Copper is a trace element that contributes to metabolical and neurological actions of metalloenzymes. and metalloproteins. Deficiency can lead to severe health issues, including anemia and neurological disorders, with two types identified: In atherosclerosis low dietary. copper provokes Primary Copper Deficiency (PDC) and Secondary Copper Deficiency (SDC) acts as a result of interaction. with other minerals. Copper transporters, when underregulated, lead to disparate overall health. Copper deficiency decrease production. in sheep in a big way thus needs to be checked regularly and the animals supplemented. with the mineral. Early detection and management of the issues are underlined by this study, especially targeting the soil and forage mineral content. This study assessed 150 lambs in Salah al-Din city from June 2 to October 15, 2024, categorized. into three groups: a control group (50 healthy lambs), a subclinical group (50 lambs with insufficient copper), and a clinical group (50 lambs with copper deficiency). Blood samples were collected via the external jugular vein and centrifuged to prepare. serum, which was stored at -20˚C. Biochemical analysis measured. levels of copper, iron, calcium, phosphorus, superoxide dismutase. (SOD), and ceruloplasmin. Thus, the means of copper, iron, calcium, phosphorus, ceruloplasmin, SOD in the studied lamb groups were significantly different, p<0.000. The clinical group consistently exhibited the lowest levels for these parameters: copper – 0,38±0,193 μg/L; iron – 105,39±24,462 μg/dL; calcium – 4,76±2,076 mg/dL; phosphorus – 4,56±0,559 mg/dL; ceruloplasmin – 6,60±4,180 mg/dL; and SOD – 34,20±11,938 UI The post hoc tests also revealed that there was significant difference between the groups. which showed the serious effects of copper deficiency in growing lambs. this study, conclude the most numerous nutrition problems of lambs in Salah Al-Din are deficiency. of copper, which reflected the overall health and productive performance and cause anemia. and developmental disorders